Factors Affecting C02 Emission in Vietnam: a Panel Data Analysis - Thanh, Le Trung; Khuong, Nguyen Duc (Organizations and Markets in Emerging Economies, 2017)
The purpose of this study is to investigate the major factors in the process of economic growth that influence the carbon dioxide (CO2) emission in Vietnam. An Autoregressive Distributed Lag (ARDL) model was used to evaluate the impact based on Environmental Kuznets curve (EKC) and Pollution haven hypothesis (PHH) in 1990–2011. The results indicate that the economic growth, energy consumption, financial development and trade openness  positively influence the CO2 emissions, whereas foreign direct investment has a negative impact in the short term. Coefficient of joining ASEAN is not statistically significant. The findings of this study also support the validity of EKC and PHH in the Vietnamese economy. Therefore, it is important to use green energy, examine requirements for foreign investment and adopt trade-related measures and policies to increase environmental protection.
Keywords: Environmental Kuznets Curve hypothesis; pollution haven hypothesis; economic growth; CO2 emission